Myelin Oligodendrocyte Glycoprotein: Deciphering a Target in Inflammatory Demyelinating Diseases - Peschl, Patrick; Bradl, Monika; Höftberger, Romana; Berger, Thomas; Reindl, Markus (Frontiers in Immunology, 2017)
Myelin oligodendrocyte glycoprotein (MOG), a member of the immunoglobulin (Ig) superfamily, is a myelin protein solely expressed at the outermost surface of myelin sheaths and oligodendrocyte membranes. This makes MOG a potential target of cellular and humoral immune responses in inflammatory demyelinating diseases. Due to its late postnatal developmental expression, MOG is an important marker for oligodendrocyte maturation. Discovered about 30 years ago, it is one of the best-studied autoantigens for experimental autoimmune models for multiple sclerosis (MS). Human studies, however, have yielded controversial results on the role of MOG, especially MOG antibodies, as a biomarker in MS. But with improved detection methods using different expression systems to detect antibodies in patients´ samples, this is meanwhile no longer the case. Using cell-based assays with recombinant full-length, conformationally intact MOG, several recent studies have revealed that MOG antibodies can be found in a subset of predominantly pediatric patients with acute disseminated encephalomyelitis (ADEM), aquaporin-4 (AQP4) seronegative neuromyelitis optica spectrum disorders (NMOSD), monophasic or recurrent isolated optic neuritis or transverse myelitis, in atypical MS and in N-methyl-D-aspartate receptor (NMDAR)-encephalitis with overlapping demyelinating syndromes. Whereas MOG antibodies are only transiently observed in monophasic diseases such as ADEM and their decline is associated with a favorable outcome, they are persistent in multiphasic ADEM, NMOSD or recurrent optic neuritis or myelitis. Due to distinct clinical features within these diseases it is controversially disputed to classify MOG antibody positive cases as a new disease entity. Neuropathologically, the presence of MOG antibodies is characterized by MS-typical demyelination and oligodendrocyte pathology associated with antibodies and complement. However, it remains unclear whether MOG antibodies are a mere inflammatory bystander effect or truly pathogenetic. This article provides deeper insight into recent developments, the clinical relevance of MOG antibodies and their role in the immunpathogenesis of inflammatory demyelinating disorders.